Superorganism toward a new social contract for our endangered species - Corning, Peter A. 1935- (Cambridge elements, 2023)
As evidence of our global survival crisis continues to mount, the expression 'too little, too late' comes to mind. We all live in an interdependent world which has an increasingly shared fate. We are participants in an emerging global 'superorganism' that is dependent on close cooperation. Indeed, positive synergy (cooperative effects) has been the key to our evolutionary success as a species. However, our ultimate fate is now in jeopardy. Going forward, we must either create a more effective global society (with collective self-governance) or our species will very likely be convulsed by mass starvation, waves of desperate migrants, and lethal social conﬂict. The greatest threat we may face is each other, and a regression into tribalism and violent conﬂict. This Element has a more hopeful prescription for a new global social contract. It is based on the many examples of superorganisms - socially organized species - in the natural world, and in evolution